Neighbourhood social conduits and resident social cohesion. (January 2019) - Wickes, Rebecca; Zahnow, Renee; Corcoran, Jonathan; Hipp, John R
Given the importance of the neighbourhood context for residents' social cohesion, the current study examines the association between types of social and non-social places on three indicators of social cohesion: neighbour networks, social cohesion and neighbourhood attachment. We spatially integrate data from the census, topographic databases and a 2012 survey of 4132 residents from 148 neighbourhoods in Brisbane, Australia, and employ multilevel models to assess whether the variation in resident reports of social cohesion is attributable to land uses that function as neighbourhood social conduits. We also consider the degree to which neighbourhood fragmentation affects our indicators of social cohesion. Our findings reveal that even after controlling for the socio-demographic context of the neighbourhood and a range of individual and household control variables, residents' reports of social cohesion are significantly associated with the types of social conduits, the diversity of land use and the degree of neighbourhood fragmentation.